2017
DOI: 10.1080/07448481.2017.1312411
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of two approaches to prevention of mental health problems in college students: Enhancing coping and executive function skills

Abstract: Brief stress management interventions targeting coping and executive function may benefit college students at risk for psychopathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 51 publications
4
37
0
2
Order By: Relevance
“…Although this study is a cross‐sectional exploration of emerging adults’ mental health and may not include the development of internalizing and externalizing problems over time, attending college is a time of transition for emerging adults, putting them at higher risk for mental health problems (Bettis et al., ). Students may seek additional support from their parents during this time to successfully navigate the changes necessary to avoid mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…Although this study is a cross‐sectional exploration of emerging adults’ mental health and may not include the development of internalizing and externalizing problems over time, attending college is a time of transition for emerging adults, putting them at higher risk for mental health problems (Bettis et al., ). Students may seek additional support from their parents during this time to successfully navigate the changes necessary to avoid mental health problems.…”
Section: Discussionmentioning
confidence: 99%
“…The role of executive functioning in the etiology of mental health conditions has spurred increased focus on this key construct in intervention development efforts [ 55 57 ]. A cognitive-behavioral executive functioning intervention specific to ASD, entitled Unstuck and On Target ( UOT [ 58 ]), was developed for use in community school service settings with students with ASD.…”
Section: Executive Functioning As a Target Of Ebismentioning
confidence: 99%
“…The literature suggested that mindful practices could have a positive impact on student learning [6,[13][14], on reducing emotional exhaustion and improving workplace satisfaction and effectiveness [15][16], and on supporting mental health [11,17].…”
Section: Literature Reviewmentioning
confidence: 99%